APLIKASI MHEALTH COVID-19 DI INDONESIA: ANALISIS KONTEN MENGGUNAKAN MOBILE APLICATION RATING SCALE (MARS) - Maharani Bening; Kunto Adi Wibowo; Ikhsan Fuady (LPPM STMIK STIKOM Indonesia, 2021)
It has been a year since the first COVID-19 cases in Indonesia and the development of COVID-19 health applications has grown significantly during that time. However, there has not been found research to analyze such an application in Indonesia. This study aims to evaluate the mHealth COVID-19 application in Indonesia application store, which will eventually become a reference for all researchers related to the mhealth application development in Indonesia. The researchers used COVID-19-related keywords to identify apps on iOS and Android devices. There were 17 applications selected for this research, and the applications' quality were assessed by two coders using the Mobile App Rating Scale (MARS). The search results totaled 842 applications, 19 of which met the researcher's criteria, and 17 applications were found to be assessed. This research was using the Krippendorff coefficient alpha (α) to calculate the reliability value of the agreement between coders. The result showed that PeduliLindungi applications had the highest (4.2/5) of the average MARS score, and the MARS scores of 14 applications were unacceptable (<3.0), which explained that most of the COVID-19 related apps in Indonesia are of low quality. Also, this research implies that the information-related features should be the next focus for overall quality improvement of the Indonesian mHealth application in the future.